Penerapan Prinsip Mengenali Pengguna Jasa oleh Notaris dalam Pencegahan Tindak Pidana Pencucian Uang - Bunga Desyana Pratami (Pusat Pelaporan dan Analisis Transaksi Keuangan (PPATK), 2025)
Notaries often handle high-value transactions that may be exploited for illicit purposes. Accordingly, notarial application of the Know Your Customer (KYC) principle is a key element of Indonesia’s anti–money laundering and counter–terrorist financing (AML/CTF) framework. This study examines how notaries implement KYC and identifies factors affecting compliance with the submission of suspicious transaction reports (STRs) via the GoAML platform. A socio-legal design with qualitative methods was employed, combining primary evidence from surveys and in-depth interviews with notaries in an anonymized jurisdiction and secondary materials from relevant laws and scholarly literature. The results show uneven levels of knowledge, comprehension, attitudes, and legal conduct among notaries in applying KYC obligations. Although the regulatory basis is in place, implementation remains constrained by limited technical capacity, administrative workload, and the persistently low volume of STR reporting. These findings point to a continuing disconnect between formal requirements and field-level practice. The study highlights the importance of sustained capacity-building, more effective oversight, and stronger coordination among government agencies, professional associations, and legal education institutions to enhance KYC implementation and strengthen the AML/CTF regime.